Standing balance of professional ballet dancers and non-dancers under different conditions - Janura, Miroslav; Procházková, Markéta; Svoboda, Zdeněk; Bizovská, Lucia; Jandová, Soňa; Konečný, Petr (PloS one, 2019)
Ballet training has been reported to positively influence balance ability. It is not entirely clear how improved balance ability manifests under standing conditions with different demands on postural control. The aim of the study was to compare balance of ballet dancers and non-dancers in a unipedal stance under different conditions. Twenty-five professional ballet dancers and twenty-five controls completed four unipedal standing balance tests: firm surface with eyes open and closed; foam mat surface with eyes open; and firm surface with eyes open immediately after performing ten 360° whole-body turns. The centre of pressure (COP) data were obtained with a force platform and the direction-specific standard deviations, velocities, and sample entropy of the COP displacement were computed. A three-way analysis of variance was used to compare groups, genders, and conditions. For standing immediately after performing ten turns, the postural sway parameters were significantly larger in the control group compared to the ballet dancers in both men and women. In this stance condition the values of postural sway and COP velocities in the control group were larger in the men compared to the women. For both genders in the control group all postural sway and COP velocity parameters were larger in standing with eyes closed and standing after performing 10 turns compared to standing with eyes open on both firm and foam surface. In the ballet dancers all COP velocity parameters were larger in standing with eyes closed compared to all other conditions. The results from the present study indicate that professional ballet dancers do not have a better general balance ability than untrained subjects.
Keywords: dospělí; mladý dospělý; Postural Balance; funkční lateralita; lidé; posturální rovnováha; mužské pohlaví; postura těla; Female; Male; Functional Laterality; Posture; Young Adult; Dancing; Adult; tanec; ženské pohlaví; Humans